2022
DOI: 10.1002/arcp.1084
|View full text |Cite
|
Sign up to set email alerts
|

A review and future avenues for psychological ownership in consumer research

Abstract: Research on psychological ownership is prevalent in the consumer domain. This article details the theoretical core of psychological ownership, integrating research in consumer psychology and marketing. The underlying motivations behind psychological ownership are also considered as well as the antecedents and consequences of feeling ownership. This article discusses how consumers signal and infer a sense of ownership, acknowledging that the characteristics of the target of ownership vary greatly to include phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 227 publications
0
21
0
Order By: Relevance
“…However, investment should be construed as broader than Boyer's discussion of physical labor, as it can include emotions, ideas, and (non-labor) time. Indeed, the psychological ownership literature suggests that many of these types of investments are sufficient to trigger feelings of ownership (see, e.g., Peck & Luangrath, 2023, for an overview).…”
Section: Introductionmentioning
confidence: 99%
“…However, investment should be construed as broader than Boyer's discussion of physical labor, as it can include emotions, ideas, and (non-labor) time. Indeed, the psychological ownership literature suggests that many of these types of investments are sufficient to trigger feelings of ownership (see, e.g., Peck & Luangrath, 2023, for an overview).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that naming a robot leads consumers to unconsciously personify the robot and that this personification strategy enhances consumer satisfaction and customer experience with the service robot (Waytz et al, 2010;Yam et al, 2021a, b). Consumers naming products themselves can increase their psychological ownership of the product, which in turn enhances their evaluation of the product (Peck and Luangrath, 2023;Stoner et al, 2018). Accordingly, this study proposes the following:…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Third, this study examined the moderating effect of product involvement. According to previous studies (for a review, Jussila et al, 2015;Peck & Luangrath, 2022;Pierce et al, 2003), the degree that psychological ownership occurs depends on the target attributes. Jussila et al (2015) stated, "Quite obviously, if the target is not attractive or does not capture the individual's attention, psychological ownership for that target cannot develop" (p. 127).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Pierce et al (2003) stated that an association with the object is important for psychological ownership to occur. According to Peck and Luangrath (2022), one of the antecedents to psychological ownership is to have more information and knowledge about a target. These findings suggest that the degree of involvement with a product moderates the effect of haptic imagery on psychological ownership; however, this has not been empirically examined.…”
Section: Introductionmentioning
confidence: 99%